2015
DOI: 10.1093/toxsci/kfv311
|View full text |Cite
|
Sign up to set email alerts
|

Human Sulfotransferases Enhance the Cytotoxicity of Tolvaptan

Abstract: Tolvaptan, a vasopressin receptor 2 antagonist used to treat hyponatremia, has recently been reported to be associated with liver injury. Sulfotransferases (SULTs) have been implicated as important detoxifying and/or activating enzymes for numerous xenobiotics, drugs, and endogenous compounds. To characterize better the role of SULTs in tolvaptan metabolism, HEK293 cells stably overexpressing 12 human SULTs were generated. Using these cell lines, the extent of tolvaptan sulfate formation was assessed by revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, SULT2A1 is involved in the individual genetic disposition, species differences, and organotropisms for toxicological effects of chemicals 40 . The activity modulation of SULT2A1 with the aid of selective inhibitor may prove to be preventive or therapeutic method for metabolic activation mediated toxicological effects 41 , 42 , 43 . Therefore, a specific activity-based probe for SULT2A1 is a valuable tool for measuring the function level of SULT2A1 and searching for the novel therapeutic agent that targeted to SULT2A1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SULT2A1 is involved in the individual genetic disposition, species differences, and organotropisms for toxicological effects of chemicals 40 . The activity modulation of SULT2A1 with the aid of selective inhibitor may prove to be preventive or therapeutic method for metabolic activation mediated toxicological effects 41 , 42 , 43 . Therefore, a specific activity-based probe for SULT2A1 is a valuable tool for measuring the function level of SULT2A1 and searching for the novel therapeutic agent that targeted to SULT2A1.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to evaluate SULT1C3 (isoform d) activity have indicated that this enzyme can sulfonate large benzylic alcohols, including metabolites of polycyclic aromatic hydrocarbons, and the steroid-related compounds a-zearalenol and lithocholic acid (Allali-Hassani et al, 2007;Meinl et al, 2008a). Also, a recent study reported that SULT1C3 had the lowest K m and highest V max of 12 human SULTs tested for sulfonation of tolvaptan, which is a selective vasopressin V 2 -receptor antagonist that possesses a benzylic hydroxy group (Fang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sulfation often results in the inactivation of the substrates or reduced potency of ligands (Strott, 2002;Bjerregaard-Olesen et al, 2015) but with some exceptions. Their abundance in the liver and wide range of substrates suggest SULTs may act as important mediators for the development of liver diseases, such as hepatocellular carcinoma (Xie et al, 2017;Zou et al, 2017), liver fibrosis (Hardwick et al, 2013;Krattinger et al, 2016;Yetti et al, 2018), and drug-induced liver injury (Fang et al, 2016). Therefore, in this review we focus on the roles of the human and rodent SULTs in liver diseases.…”
Section: Introductionmentioning
confidence: 99%